Review Of The Implementation Of Outpatient Registration Services At Katobengke Health Center - Afrianda, Ninis; Sri Wahyuni; Selvi Mayang Sari (International Journal of Multidisciplinary Learners, 2025)
Registration is a service process carried out by the Health Center to obtain the identity of patients who come. This study aims to evaluate the implementation of outpatient registration at the Katobengke Health Center in 2024. Based on initial observations, there are several obstacles in the registration system. One problem that often arises is the loss of network connection, which forces officers to record data manually when patients seek treatment. In addition, patients often do not bring important documents such as Identity Cards (KTP), Family Cards (KK), and Treatment Cards, which also hinder the registration process. In this study, the population studied consisted of 3 registration officers. The method used is a descriptive approach with a qualitative approach, and data were collected through interviews and observations. The population that became the focus was 3 officers who worked in the outpatient registration section. The results of the study showed that in terms of human resources, the number of medical record officers in the registration unit was still relatively lacking, because there was only one officer who had a D3 medical record education background, while one other officer had a different background or S1 public health. In terms of methods , there was no SOP for using the E-Puskesmas Application so that the old registration flow was still used. In terms of materials , the internet network connection and server were sometimes problematic so that it could hinder service time when registering patients. In terms of machines, the number of computers and printers was currently sufficient in the medical record and registration units, in addition, the condition of the computers and printers was good and could be used and there were no problems during use. In terms of money , the budget for the needs of medical recorders and registration officers was already available. It is recommended that a Wi-Fi network be added and the E-Puskesmas application server be re-evaluated